HUBUNGAN PERLAKUAN DELTAMETRIN PADA AIR MINUM BERBAGAI KONSENTRASI TERHADAP KANDUNGAN RESIDU DELTAMETRIN PADA DARAH, HATI, DAN DAGING AYAM BROILER - , CAHYA PURNAMASARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Pesticide is an important material in agriculture or livestock sector, especially in eradicating insects. Non procedural pesticide usage can lead to issues such as the presence of residue in agriculture/livestock products. This study aimed to determine the effect of various concentrations of deltametrin treatment in drinking water on the residue content in the blood, liver, and meat of broilers. Nine broilers were divided into three groups. Group 1 was the control, Group 2 was group given deltametrin 5 mg/L in drinking water, and Group 3 was group given deltametrin 10 mg/L in drinking water. Broilers were kept in Education and Training Unit of Animal Health (UP2KH) cage for 35 days and residue inspection in blood, liver, and meat was conducted after the harvest. Deltametrin residue analysis was performed at the Laboratory of Pharmacology of FKH UGM. Analysis of correlation showed that there was a significant linear relationship between various deltametrin concentration and residue concentration in meat (r>0,9